Evaluation of Online Learning at Public Junior High School 2 Gorontalo - Botutihe, Nuzlan; Mohi, Widya Kurniati (Journal of Education Review Provision, 2022)
The purpose of this research is to assess online learning at SMP Negeri 2 Gorontalo due to the COVID-19 pandemic. A research that was exploratory, descriptive, and used a qualitative research design was used for data collection. This study employed the use of interviews, observations and secondary data collection. The study shows that online learning at the school had various problems experienced such as low user engagement, no discipline, poor direct contact between the students and the teachers, improper training techniques, and technical difficulties. From the same factors, the standard of education as well as student performance was affected negatively.